2021
DOI: 10.1029/2020gl091624
|View full text |Cite
|
Sign up to set email alerts
|

Shear‐Wave Velocity Structure of the Southern African Upper Mantle: Implications for Craton Structure and Plateau Uplift

Abstract: We present a 3D shear‐wave velocity model of the southern African upper mantle developed using 30–200 s period Rayleigh waves recorded on regional seismic networks spanning the subcontinent. The model shows high velocities (∼4.7–4.8 km/s) at depths of 50–250 km beneath the Archean nucleus and several surrounding Paleoproterozoic and Mesoproterozoic terranes, placing the margin of the greater Kalahari Craton along the southern boundary of the Damara Belt and the eastern boundaries of the Gariep and Namaqua‐Nata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 53 publications
(104 reference statements)
5
21
0
Order By: Relevance
“…The Zimbabwe Craton is imaged as a highly resistive structure with the presence of crustal conductive structures, which may be due to presence of graphite and/or sulfide (Khoza et al, 2013a). The observed high resistivity structure of the Zimbabwe Craton is consistent with results from velocity models, which show highvelocity anomalies beneath the Zimbabwe Craton (Ortiz et al, 2019;Fadel et al, 2020;White-Gaynor et al, 2021). Another feature of note along F-F′ is the highly conductive structure, which may be due to iron enrichment during the Bushveld Complex beneath the Kaapvaal Craton and the Limpopo Belt.…”
Section: The Electrical Conductivity Modelsupporting
confidence: 78%
See 1 more Smart Citation
“…The Zimbabwe Craton is imaged as a highly resistive structure with the presence of crustal conductive structures, which may be due to presence of graphite and/or sulfide (Khoza et al, 2013a). The observed high resistivity structure of the Zimbabwe Craton is consistent with results from velocity models, which show highvelocity anomalies beneath the Zimbabwe Craton (Ortiz et al, 2019;Fadel et al, 2020;White-Gaynor et al, 2021). Another feature of note along F-F′ is the highly conductive structure, which may be due to iron enrichment during the Bushveld Complex beneath the Kaapvaal Craton and the Limpopo Belt.…”
Section: The Electrical Conductivity Modelsupporting
confidence: 78%
“…Their study suggests that the low seismic wave velocity anomaly is linked to compositional changes in the mantle due to iron enrichment from the formation of the Bushveld Complex. Similarly, other seismic investigations, including the P and S wave velocity study by Ortiz et al (2019) and the shear-wave velocity study by White-Gaynor et al (2021), show a region of low velocities beneath the Bushveld Complex in the Kaapvaal Craton. Ortiz et al (2019), supporting Fouch et al (2004, argue that the low velocities anomalies observed beneath the Okwa Block, Magondi Belt and Limpopo Belt, which are extensions of the Bushveld Complex, are results of the modification of the composition of the mantle material from the magmatic event.…”
Section: The Maltahohe Microcratonmentioning
confidence: 55%
“…Since kimberlite compositions confirm the presence of a thick depleted lithosphere up to about 80 Ma (Griffin, O’Reilly, Natapov, & Ryan, 2003), its widespread refertilization must have occurred afterward (Celli et al., 2020). Lithospheric thickness is still debated (e.g., Sodoudi et al., 2013; White‐Gaynor et al., 2021), with estimates ranging from up to 300 km (James et al., 2001) to 170 km (Priestley et al., 2008). Concordant with the latter estimate, temperatures close to or above 1300°C deeper than 150 km beneath most parts of the Kaapvaal craton indicate lithosphere thicknesses between 150 and 200 km.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, the African continent comprises several cratons (Figure 1) whose lithospheric thickness, physical state, and evolution are still a matter of debate (Boyce et al., 2021; Celli et al., 2020; Hu et al., 2018; Jessell et al., 2016; White‐Gaynor et al., 2021). Here, we apply the previously mentioned approach to model the thermal and compositional state of the cratonic lithosphere of Africa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation